Gambaran pengetahuan ibu tentang makanan pendamping ASI (MP-ASI) pada anak usia 6-24 bulan - Putri Eka Sudiarti; Meri Neherta; Deswita Deswita (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Mother's knowledge about complementary foods on infant children aged 6-24 months in Kampar, Riau-IndonesiaBackground: Problems with children’s nutritional status can cause mortality and morbidity in children. The problem of nutritional status in children under five is caused by the lack of mother’s knowledge about complementary feeding. Purpose: This study aims to determine an overview of mother’s knowledge about complementary foods on infant children aged 6-24 months. Methods: The study method used descriptive method. The population of the study was mothers who had children aged 6-24 months in the Kampar District. Sampling technique used Random sampling technique with Multi Stage sampling obtained a sample of 75 people in the Tambang and Bangkinang Public health center. The study instrument used questioner. The analysis technique used descriptive quantitative. Results: The results of study showed that 64% of mothers had sufficient knowledge and 36% of mothers had moderate knowledge. Conclusion: The conclusion of the study was the majority of mothers' knowledge who had children aged 6-24 months about complementary foods on infant were in sufficient range. It is necessary to conduct nutritional education on complementary feeding to increase mothers’ knowledge about complementary feeding.Keywords: Mothers knowledge; Complementary foods; Infant children; Aged 6-24 monthsPendahuluan: Permasalahan status gizi anak dapat menyebabkan mortalitas dan morbiditas pada anak. Permasalahan status gizi pada anak usia balita salah satunya disebabkan oleh rendahnya pengetahuan ibu mengenai MP-ASI.Tujuan: Diketahui gambaran pengetahuan ibu mengenai MP-ASI anak usia 6-24 bulan.Metode: Metode penelitian menggunakan metode deskriptif. Populasi penelitiana adalah ibu yang memiliki anak usia 6-24 bulan di wilayah Kabupaten Kampar. Teknik pengambilan Sampel menggunakan teknik randome sampling dengan Multi Stage Sampling dan didapatkan sampel berjumlah 75 orang pada wilayah Puskesmas Tambang dan Bangkinang. Instrumen penelitian menggunakan kuisioner. Teknik analisa menggunakan deskriptif kuantitatif.Hasil: Hasil penelitian menunjukkan bahwa sebesar 64% ibu memiliki pengetahuan cukup dan 36% persen ibu memiliki pengetahuan sedang.Simpulan: Penelitian didapatkan bahwa mayoritas pengetahuan ibu anak usia 6-24 bulan mengenai MP-ASI berada pada rentang cukup. Perlu dilakukannya edukasi gizi mengenai MP-ASI untuk meningkatkan pengetahuan ibu mengenai MP-ASI.